Bending behaviour of glulam beams reinforced with carbon FRP plates - Glišović, Ivan; Stevanović, Boško; Petrović, Miloš (Journal of Civil Engineering and Management, 2015)
The idea of reinforcing glued laminated timber (glulam) beams came in response to the need to improve the mechanical properties, as well as to ensure higher reliability of this type of structural elements. This paper describes an experimental program which examines the reinforcement in flexure of glulam beams with carbon fibre reinforced plastic (CFRP) plates. Fifteen beams reinforced with CFRP at the tension side and five unreinforced control beams were instrumented and tested to failure in a four-point bending configuration. The mechanical properties of reinforced beams are compared to those of unreinforced beams with regard to the load-deflection behaviour, failure mode, ultimate load capacity, stiffness and strain distribution. The experimental results demonstrated the beneficial effect of the proposed reinforcing solution in terms of strength, stiffness and ductility.